Positive electrode lithium supplement agent and preparation method and application thereof

By using lithium supplement agent combined with lithium-rich lithium ferrate matrix and organic lithium supplement coating in the positive electrode material of lithium battery, the problem of active lithium loss during the first charge and discharge of lithium batteries is solved, the battery capacity and cycle stability are improved, and safety risks are reduced.

CN119517989APending Publication Date: 2025-02-25HU NAN SHENG RONG KE JI YOU XIAN GONG SI

Patent Information

Application Number
CN202411620066.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the first charging and discharging of existing lithium batteries, a large amount of active lithium will be lost due to the formation of the SEI film, resulting in reduced battery capacity, low Coulomb efficiency and poor circulation performance.

Method used

A positive electrode lithium supplement agent combined with a lithium-rich ferrate matrix and an organic lithium-fuel coating is used to form a stable organic lithium-fuel coating layer through spray drying and sintering processes, reducing the contact between lithium-fuel lithium-fuel and air, and improving its stability and lithium ion transmission effect.

Benefits of technology

It effectively reduces the residual alkali amount of lithium lithium ferrate, improves its stability and lithium ion transmission effect, improves the initial capacity and cycle stability of the battery, and reduces safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery materials, and discloses a positive electrode lithium supplement agent and a preparation method and application thereof. The positive electrode lithium supplement agent comprises a lithium-rich lithium ferrite matrix and an organic lithium supplement coating layer, wherein the organic lithium supplement coating layer coats at least part of the surface of the lithium-rich lithium ferrite matrix; and the organic lithium-supplementing coating layer is any one or two of lithium oxalate and lithium squarate. The organic lithium supplement coating layer provided by the invention can prevent the lithium-rich lithium ferrite from being in contact with air, the stability of the lithium-rich lithium ferrite is improved while the residual alkali is reduced, the lithium ion transmission effect of the lithium-rich lithium ferrite is improved, and the lithium supplement effects of the lithium-rich lithium ferrite and the organic lithium supplement agent can be utilized to improve the capacity and the cycling stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery materials and relates to a lithium supplement agent, and in particular to a positive electrode lithium supplement agent and a preparation method and application thereof. Background Art

[0002] Most high-capacity lithium batteries will lose a large amount of active lithium due to the formation of SEI film during the first charge and discharge. This loss will cause permanent loss of lithium in the positive electrode material, resulting in reduced battery capacity, reduced coulombic efficiency, and poor cycle performance. Lithium replenishment technology is an effective means to improve the above problems. It can effectively solve the problem of low first coulombic efficiency and improve the capacity and cycle stability of the battery.

[0003] In the prior art, the commonly used lithium supplement material is lithium-rich iron oxide, which can release four equivalent lithium ions, has a high theoretical capacity (726mAh / g), and has extremely poor reversibility (Coulomb efficiency <10%), making it an ideal lithium supplement. However, lithium-rich iron oxide is unstable in the air and easily absorbs moisture to form inactive Li x Fe y O z As well as residual alkali (LiOH), this not only reduces its electrochemical activity, but the presence of residual alkali can also easily lead to battery gas production, posing a safety hazard. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a positive electrode lithium replenisher; in the second aspect, the present invention provides a method for preparing the positive electrode lithium replenisher; in the third aspect, the present invention provides a positive electrode active material; in the fourth aspect, the present invention provides a positive electrode; in the fifth aspect, the present invention provides a battery.

[0005] In a first aspect, the present invention provides a positive electrode lithium replenisher, comprising a lithium-rich lithium ferrite matrix and an organic lithium replenisher coating layer, wherein the organic lithium replenisher coating layer is coated on at least a portion of the surface of the lithium-rich lithium ferrite matrix; the organic lithium replenisher coating layer is any one or both of lithium oxalate and lithium squarate.

[0006] Preferably, the D50 of the lithium-rich lithium ferrite matrix is ​​5-35 μm; and the average coating thickness of the organic lithium-supplementing coating layer is 50-200 nm.

[0007] In a second aspect, the present invention provides a method for preparing a positive electrode lithium supplement, comprising the following steps: Step 1, dispersing lithium iron oxide particles rich in lithium iron oxide in an organic solvent and an organic acid to obtain a slurry, Step 2, spray drying slurry A to obtain solid particles; Step 3, sintering the solid particles under an inert atmosphere to obtain the positive electrode lithium supplement; The organic acid is any one or both of oxalic acid and squaric acid.

[0008] Preferably, in step 1, after dispersing the lithium iron-rich lithium ferrate particles in an organic solvent and an organic acid, an ultrasonic etching process is also included.

[0009] More preferably, the ultrasonic power is 50-300 W, the ultrasonic time is 10-60 min, and the ultrasonic etching temperature is 10-30 °C.

[0010] Preferably, the mass ratio of the lithium-rich lithium ferrite particles to the organic solvent and the organic acid is 1:0.6-5:0.001-0.02.

[0011] Preferably, the organic solvent is any one or more of methanol, ethanol, propanol and butanol.

[0012] Preferably, in step 2, the spray drying is closed spray drying, the gas provided for spray drying is an inert gas, the inert gas is any one or both of nitrogen and argon, and the spray temperature is 60 to 130°C.

[0013] Preferably, in step 3, the gas providing the inert atmosphere is any one or both of argon and nitrogen.

[0014] Preferably, when the organic acid used in step 1 is oxalic acid, in step 3, the sintering temperature is 200-480°C, and the sintering time is 2-8h; when the organic acid used in step 1 is squaric acid, in step 3, the sintering temperature is 200-700°C, and the sintering time is 2-8h.

[0015] In a third aspect, the present invention provides a positive electrode active material, comprising a matrix active material and the positive electrode lithium replenisher mentioned above or the positive electrode lithium replenisher prepared by the above preparation method.

[0016] Preferably, the matrix active material is any one or more of lithium cobalt oxide, lithium nickel oxide, nickel-cobalt-manganese ternary, lithium iron phosphate, and lithium manganese iron phosphate.

[0017] In a fourth aspect, the present invention provides a positive electrode comprising the positive electrode active material.

[0018] In a fifth aspect, the present invention provides a battery comprising the above-mentioned positive electrode.

[0019] Compared with the prior art, the above one or more technical solutions of the present invention have at least one of the following beneficial effects: (1) The organic lithium replenishing coating provided by the present invention can prevent the lithium-rich ferrite from contacting with air, reduce residual alkali and improve the stability of the lithium-rich ferrite, improve the lithium ion transmission effect of the lithium-rich ferrite, and utilize the lithium replenishing effect of both the lithium-rich ferrite and the organic lithium replenisher to improve the capacity and cycle stability of the battery.

[0020] (2) The present invention uses organic acid to etch lithium-rich iron oxide. During the etching process, the organic acid reacts with the residual alkali on the surface of the lithium-rich iron oxide to generate the target organic lithium-supplementing coating material. The etching is combined with the sintering process to help improve the structural stability between the lithium-rich iron oxide and the organic lithium-supplementing coating. DETAILED DESCRIPTION

[0021] The present invention provides the following specific technical solutions.

[0022] In a first aspect, the present invention provides a positive electrode lithium replenisher, comprising a lithium-rich lithium ferrite matrix and an organic lithium replenisher coating layer, wherein the organic lithium replenisher coating layer is coated on at least a portion of the surface of the lithium-rich lithium ferrite matrix; the organic lithium replenisher coating layer is any one or both of lithium oxalate and lithium squarate.

[0023] The combination of lithium-rich lithium iron oxide and an organic lithium-supplementing coating layer can reduce the interfacial impedance of lithium-rich lithium iron oxide and improve the lithium ion transmission effect of lithium-rich lithium iron oxide. Using it in the positive electrode material can improve the initial specific capacity and cycle stability of the battery.

[0024] Preferably, the D50 of the lithium-rich lithium ferrite matrix is ​​5-35 μm; and the average coating thickness of the organic lithium-supplementing coating layer is 50-200 nm.

[0025] If the coating layer is too thin, the effect of reducing residual alkali is not significant, and if the coating layer is too thick, the capacity of the substrate itself will be affected.

[0026] In a second aspect, the present invention provides a method for preparing a positive electrode lithium supplement, comprising the following steps: Step 1, dispersing lithium iron oxide particles rich in lithium iron oxide in an organic solvent and an organic acid to obtain a slurry, Step 2, spray drying slurry A to obtain solid particles; Step 3: sintering the solid particles under an inert atmosphere to obtain the positive electrode lithium supplement.

[0027] The organic acid is any one or both of oxalic acid and squaric acid.

[0028] The lithium-rich iron ore material is etched with an organic acid. During the etching process, the organic acid reacts with the residual alkali on the surface of the lithium-rich iron ore to form an organic lithium-supplementing coating layer. The organic lithium-supplementing coating layer can be evenly coated on the surface of the lithium-rich iron ore particles. Combined with the subsequent sintering process, it helps to improve the structural stability between the lithium-rich iron ore and the organic lithium-supplementing coating layer.

[0029] Preferably, in step 1, after dispersing the lithium iron-rich lithium ferrate particles in an organic solvent and an organic acid, an ultrasonic etching process is also included.

[0030] More preferably, the ultrasonic power is 50-300 W, the ultrasonic time is 10-60 min, and the ultrasonic etching temperature is 10-30 °C.

[0031] The ultrasonic process is used during etching to enhance the etching effect, which is beneficial to the full reaction between the organic acid and the residual alkali on the surface of the lithium-rich lithium iron oxide, and further reduces the amount of residual alkali on the surface of the lithium-rich lithium iron oxide.

[0032] Preferably, the mass ratio of the lithium-rich lithium ferrite particles to the organic solvent and the organic acid is 1:0.6-5:0.001-0.02; the mass concentration of the organic solvent is 60%-100%; and the mass concentration of the organic acid is 1%-10%.

[0033] Preferably, the organic solvent is any one or more of methanol, ethanol, propanol and butanol.

[0034] Preferably, in step 2, the spray drying is closed spray drying, the gas provided for spray drying is an inert gas, the inert gas is any one or both of nitrogen and argon, and the spray temperature is 60 to 130°C.

[0035] Preferably, in step 3, the gas providing the inert atmosphere is any one or both of argon and nitrogen.

[0036] Preferably, when the organic acid used in step 1 is oxalic acid, in step 3, the sintering temperature is 200-480°C, and the sintering time is 2-8h; when the organic acid used in step 1 is squaric acid, in step 3, the sintering temperature is 200-700°C, and the sintering time is 2-8h.

[0037] If the sintering temperature is too high, the organic lithium supplement will decompose, resulting in higher residual alkali on the surface of the material, reducing the cyclic stability of the material. If the sintering temperature is too low, the organic acid cannot react with the residual lithium on the surface, and the connection between the coating and the substrate is unstable, so the coating is very easy to fall off.

[0038] Preferably, the gas providing the inert atmosphere is any one of argon and nitrogen, or two or more thereof.

[0039] In a third aspect, the present invention provides a positive electrode active material, comprising a matrix active material and the positive electrode lithium replenisher mentioned above or the positive electrode lithium replenisher prepared by the above preparation method.

[0040] Preferably, the matrix active material is any one or more of lithium cobalt oxide, lithium nickel oxide, nickel-cobalt-manganese ternary, lithium iron phosphate, and lithium manganese iron phosphate.

[0041] In a fourth aspect, the present invention provides a positive electrode comprising the positive electrode active material.

[0042] In a fifth aspect, the present invention provides a battery comprising the above-mentioned positive electrode.

[0043] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0044] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0046] Embodiment 1: A method for preparing a positive electrode lithium supplement comprises the following steps: Step 1: add 100 g of lithium-rich lithium iron oxide particles into 200 g of ethanol with a mass concentration of 90%, add 20 g of oxalic acid with a mass fraction of 5%, mix, and perform ultrasonic cleaning and etching at a power of 100 W for 25 minutes at 20° C. to obtain a slurry.

[0047] Step 2, spray drying the slurry at a drying temperature of 80° C. using nitrogen as a spray gas source to obtain solid particles; Step 3, placing the solid particles obtained in step 2 in a nitrogen atmosphere and subjecting them to heat treatment at 450° C. for 6 hours to obtain a positive electrode lithium supplement.

[0048] Embodiment 2: A method for preparing a positive electrode lithium supplement comprises the following steps: Step 1: add 150 g of lithium-rich lithium iron oxide particles into 320 g of ethanol with a mass concentration of 95%, add 23 g of 6% squaric acid and mix, and perform ultrasonic cleaning and etching at a power of 110 W for 10 minutes at 25° C. to obtain a slurry.

[0049] Step 2, spray drying the slurry at a drying temperature of 90° C. using nitrogen as a spray gas source to obtain solid particles; Step 3, placing the solid particles obtained in step 2 in a nitrogen atmosphere and subjecting them to heat treatment at 450° C. for 6 hours to obtain a positive electrode lithium supplement.

[0050] Embodiment 3: A method for preparing a positive electrode lithium supplement comprises the following steps: Step 1: add 100 g of lithium-rich lithium iron oxide particles to 200 g of ethanol with a mass concentration of 85%, add 10 g of 5% squaric acid and 12 g of 5% oxalic acid, mix, and perform ultrasonic cleaning and etching at 100 W power for 60 minutes at 20°C to obtain a slurry.

[0051] Step 2, spray drying the slurry at a drying temperature of 80° C. using nitrogen as a spray gas source to obtain solid particles; Step 3, placing the solid particles obtained in step 2 in a nitrogen atmosphere and subjecting them to heat treatment at 450° C. for 6 hours to obtain a positive electrode lithium supplement.

[0052] Embodiment 4: A method for preparing a positive electrode lithium supplement agent, which is different from Example 1 in that, in step 1, the cleaning and etching time is 45 minutes, and other operations and parameters are the same as Example 1.

[0053] Embodiment 5: A method for preparing a lithium-rich arsenic iron oxide positive electrode lithium supplement agent, which is different from Example 1 in that in step 1, the organic solvent is methanol, and other operations and parameters are the same as Example 1.

[0054] Embodiment 6: A method for preparing a positive electrode lithium supplement agent, which is different from Example 1 in that, in step 3, the temperature of the heat treatment is 600° C., and other operations and parameters are the same as Example 1.

[0055] Embodiment 7: The difference from Example 1 is that the solid particles obtained in step 2 are placed in a nitrogen atmosphere and heat treated at 100° C. for 6 hours to obtain a positive electrode lithium supplement.

[0056] Comparative Example 1: The difference from Example 1 is that in step 1, 100 g of lithium-rich lithium ferrite particles are added to 200 g of ethanol with a mass concentration of 90%, and ultrasonic cleaning and etching are performed at 20° C. with a power of 100 W for 25 minutes to obtain a slurry.

[0057] Comparative Example 2: The difference from Example 1 is that in step 1, 100 g of lithium-rich lithium ferrite particles are added to 200 g of ethanol with a mass concentration of 90%, and 20 g of acetic acid with a mass fraction of 5% is added and mixed, and ultrasonic cleaning and etching are carried out at 20°C with a power of 100 W for 25 minutes to obtain a slurry.

[0058] Comparative Example 3: The difference from Example 1 is that in step 1, 100 g of lithium-rich lithium ferrite particles are added to 200 g of ethanol with a mass concentration of 90%, and 20 g of hydrofluoric acid with a mass fraction of 5% is added to mix, and ultrasonic cleaning and etching are carried out at 20°C with a power of 100 W for 25 minutes to obtain a slurry.

[0059] Comparative Example 4: The difference from Example 1 is that, in step 1, 100 g of lithium-rich lithium iron oxide particles are added to 200 g of deionized water, and 20 g of oxalic acid with a mass fraction of 5% is added to mix, and ultrasonic cleaning and etching are performed at 20° C. with a power of 100 W for 25 minutes to obtain a slurry.

[0060] The physical, chemical and electrical properties of the lithium supplements prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were tested as follows: Accurately weigh 0.3g of the lithium supplement prepared in Examples 1-7 and Comparative Examples 1-4 and put them into a 100ml clean and dry washing bottle, add 100ml of ethanol to the washing bottle and stir for 5min. After stirring, vacuum filter and collect the filtrate into a 100ml volumetric flask. Transfer 40ml of the filtrate into a titration cup; titrate with 0.01M HCl standard solution to obtain a titration curve, and record the volume of hydrochloric acid standard solution consumed in the process V1 and the volume of hydrochloric acid consumed at the end point V 0 , LiOH content = 23.94 × 0.01 × (V1-V0) / 120, the residual alkali content of the lithium supplement agents prepared in Examples 1 to 7 and Comparative Examples 1 to 4 is shown in Table 1.

[0061] Table 1 Residual alkali content of lithium supplement agents prepared in Examples 1 to 7 and Comparative Examples 1 to 4 By comparing the residual alkali on the surface of the lithium supplement agent obtained in Example 1 and Comparative Example 1, it can be seen that the residual alkali on the surface of the lithium supplement agent provided by the present invention is greatly reduced.

[0062] The lithium supplement prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were mixed and ground with carbon black and PVDF at a mass ratio of 8:1:1, and then coated on aluminum foil as the positive electrode of a lithium-ion battery. A button battery of model CR2032 was assembled in a glove box filled with argon. The negative electrode of the battery was a metal lithium sheet, the diaphragm was a polypropylene microporous membrane, and the electrolyte was 1 mol / L LiPF 6 Solution, the electrolyte solvent is EC∶DMC∶EMC=1∶1∶1(v / v / v). The button cell measurement voltage range is 2V~4.5V, the charge and discharge current is 0.05C and 0.1C, and the measured initial capacity is shown in Table 2.

[0063] Table 2 Initial capacity of batteries assembled from lithium supplements prepared in Examples 1 to 7 and Comparative Examples 1 to 4 It can be seen from Table 2 that using the lithium supplement prepared by the preparation method provided by the invention as a positive electrode material can increase the initial capacity of the battery.

[0064] By comparing Example 1 with Comparative Example 2 and Comparative Example 3 respectively, it can be seen that if the organic acid used is oxalic acid and squaric acid, on the one hand, the amount of residual alkali on the surface of the lithium supplementer is lower, and on the other hand, lithium oxalate and lithium squarate generated by the reaction of oxalic acid and squaric acid with the residual alkali on the surface of the lithium supplementer are used as coating materials to coat the lithium-rich lithium ferrite. The cooperation between the two can further improve the initial charging capacity and cycle stability of the battery.

[0065] Comparing Example 1 with Comparative Example 4, the inventors explored the reason why the solvent of deionized water affects the residual alkali on the surface of the lithium supplementer: the surface of lithium ferrite becomes more unstable after absorbing water, and the internal lithium migrates outward, resulting in higher residual alkali.

[0066] The lithium supplement agent (3 wt%), LiNi 0.6 Co 0.2 Mn 0.2 O 2 After mixing evenly, the positive electrode sheet was obtained by slurry preparation, coating, drying and rolling. A control group without adding lithium supplement was set up. 0.6 Co 0.2 Mn 0.2 O 2 After mixing graphite (80wt%), Super P (10wt%) and PVDF (10wt%), the positive electrode sheet is obtained by slurry mixing, coating, drying and rolling. After mixing graphite (90wt%), Super P (5wt%) and PVDF (5wt%), the negative electrode sheet is obtained by assembling the positive and negative electrode sheets to obtain a lithium-ion battery (the separator is a polypropylene microporous membrane, and the electrolyte is 1mol / L LiPF 6 Solution, the electrolyte solvent is EC∶DMC∶EMC=1∶1∶1). The first charge and discharge cycle conditions are as follows: 0.05C constant current charging to 4.5V at 25℃, 0.05C constant current discharging to 2.0V, then 0.5C constant current charging to 4.3V, 0.5C constant current discharging to 2.0V, and the capacity retention rate of the battery is tested after 500 charge and discharge cycles. The capacity retention rate = 500 weeks 0.5C discharge gram capacity / first 0.5C discharge gram capacity × 100%. The capacity retention rate of lithium-ion batteries is shown in Table 1.

[0067] The test results are shown in Table 1 below: Table 3 Capacity retention rate of the battery with the lithium supplement prepared in Examples 1 to 7 and Comparative Examples 1 to 4 and without the lithium supplement It can be seen from Table 3 that adding the lithium supplement prepared by the present invention into the battery can improve the cycle stability of the battery.

[0068] By comparing Example 1 with Example 7, it can be seen that the sintering temperature provided by the present invention can improve the reaction effect of residual lithium and organic acid, reduce residual alkali on the surface of the material, and improve the stability between the coating layer and the substrate, thereby improving the cycle performance.

[0069] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A positive electrode lithium supplement, characterized in that: It comprises a substrate and an organic lithium-replenishing coating layer, wherein the organic lithium-replenishing coating layer is coated on at least part of the surface of the lithium-rich ferrite substrate; the substrate is lithium-rich ferrite; the organic lithium-replenishing coating layer is any one or both of lithium oxalate and lithium squarate.

2. The positive electrode lithium supplement according to claim 1, characterized in that The D50 of the substrate is 5-35 μm; and the average coating thickness of the organic lithium supplement coating layer is 50-200 nm.

3. A method for preparing a positive electrode lithium supplement, characterized in that: The steps include: Step 1, dispersing lithium iron oxide particles rich in lithium iron oxide in an organic solvent and an organic acid to obtain a slurry, Step 2, spray drying the slurry to obtain solid particles; Step 3, sintering the solid particles under an inert atmosphere to obtain the positive electrode lithium supplement; The organic acid is any one or both of oxalic acid and squaric acid.

4. The method for preparing a positive electrode lithium supplement as claimed in claim 3, characterized in that: The mass ratio of the lithium-rich lithium ferrite particles to the organic solvent and the organic acid is 1:0.6-5:0.001-0.02; the organic solvent is any one or more of methanol, ethanol, propanol and butanol.

5. The method for preparing a positive electrode lithium supplement as claimed in claim 3, characterized in that: When the organic acid used in step 1 is oxalic acid, in step 3, the sintering temperature is 200-480°C and the sintering time is 2-8h; when the organic acid used in step 1 is squaric acid, in step 3, the sintering temperature is 200-700°C and the sintering time is 2-8h.

6. The method for preparing a positive electrode lithium supplement according to claim 3 or 5, characterized in that: In step 1, after the lithium iron-rich lithium particles are dispersed in an organic solvent and an organic acid, an ultrasonic etching process is also included; the ultrasonic power is 50-300 W, the ultrasonic time is 10-60 min, and the ultrasonic etching temperature is 10-30° C.

7. The method for preparing a positive electrode lithium supplement according to claim 3 or 6, characterized in that: In step 2, the spray drying is closed spray drying, the gas provided for spray drying is an inert gas, the inert gas is any one or more of nitrogen and argon, and the spray temperature is 60 to 130°C.

8. A positive electrode active material, characterized in that It comprises a matrix active material and the positive electrode lithium replenisher according to any one of claims 1 to 2 or the positive electrode lithium replenisher prepared by the preparation method according to any one of claims 3 to 7; the matrix active material is any one or more of lithium cobalt oxide, lithium nickel oxide, nickel cobalt manganese ternary, lithium iron phosphate, and lithium manganese iron phosphate.

9. A positive electrode, characterized in that Comprising the positive electrode active material according to claim 8.

10. A battery, characterized in that: Comprising the positive electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Positive electrode lithium supplementing material, positive electrode plate containing positive electrode lithium supplementing material and electrochemical device

    CN114175310A

  • Positive electrode material and preparation method thereof, positive electrode plate and secondary battery

    CN115939362A

  • Positive electrode lithium supplement additive and preparation method thereof

    CN116314820A

  • Lithium-supplementing additive for lithium-rich lithium ferrite positive electrode, preparation method of lithium-supplementing additive and lithium ion battery positive electrode

    CN116706273A

  • Lithium-supplementing positive electrode slurry, preparation method thereof, positive plate and lithium ion battery

    CN118676375A

Cited By

  • Lithium supplementing method of high-nickel ternary positive electrode material, product of lithium supplementing method and application of product

    CN120149591A